A Sacred Cyberspace?: Towards the Ontology of Virtual Worship - Seppälä, Serafim (Review of ecumenical studies, 2023)
Due to COVID-19 restrictions, the Orthodox Church was compelled to move its worship to online platforms. What does such a shift mean in terms of liturgical theology and ontology? To what extent, and in what sense, is participation possible online? How does the virtual space function as a liturgical space? What kind of ontological and aesthetic problems are involved? Orthodox theologians have not yet developed answers to such questions. This paper approaches the problem in the light of Pseudo-Dionysian ontology, supplemented by Alexander Schmemann’s ideas, proposing that virtual worship offers a new sub-category of liturgical reality that reflects the higher forms of reality. To paraphrase the words of Pseudo-Dionysius, cyberspace constitutes a medium in which "like represents like," though it uses formations that are "even entirely inadequate and ridiculous."